Culture and Food Security of The Mowewe Community During The Covid-19 Pandemic - La Ode Topo Jers; Erens Elvianus Koodoh; Hasniah Hasniah; Abdul Jalil; La Ode Muhammad Ruspan Takasi; Alias Alias; I Kadek Sindu (Universitas Andalas, 2021)
Food is a critical aspect of community resilience. The Covid-19 pandemic, however, has affected the natural environment, making food supply scarce and ultimately impacting economic and national stability. Despite this, the Mowewe community shares a local culture by which its people get empowered to maintain food security. Therefore, this study aims to discover and describe the local community's culture in Mowewe District in establishing a food security system. The method used was ethnography with a qualitative approach. Data were collected through participant observation, in-depth interviews, and documentation, after which the data were analyzed using qualitative descriptive techniques. The findings revealed that the local culture of the Mowewe community was built upon the concept of Mekambare, principles of gotong royong (cooperation), and ecological adaptation. The Mowewe community was of deep concern for the pattern of life balance during the pandemic. They took advantage of natural resources by clearing agricultural land to grow rice, corn, patchouli, and sago and keeping bees in the forest to produce honey for an additional source of income and immunity